If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -35 = 6x Reorder the terms: -35 + 7x = 6x Solving -35 + 7x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -35 + 7x + -6x = 6x + -6x Combine like terms: 7x + -6x = 1x -35 + 1x = 6x + -6x Combine like terms: 6x + -6x = 0 -35 + 1x = 0 Add '35' to each side of the equation. -35 + 35 + 1x = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 1x = 0 + 35 1x = 0 + 35 Combine like terms: 0 + 35 = 35 1x = 35 Divide each side by '1'. x = 35 Simplifying x = 35
| 47x-241=3 | | 3(-2)-5y=10 | | 35x-250=10 | | -3x+-22=8 | | 15q+-4r=62 | | 76x*220=3230 | | 2x/48=3:12 | | 878574868x=8384748372929 | | 6/11y=19 | | 2*(1/10) | | .002=1/x | | (3r^5+5r^2-4)-(-7r^5-3r^2+16)= | | F(x)=(3x-7) | | 3c+2d=8 | | 2y-2=3 | | 3x-2+5=2(5x-4) | | z^3-j=0 | | 7.50x+8y=93.50 | | 4x=0.9 | | 6a-4b-2a+24b= | | 6-2(x+8)=6x-26 | | 5(2-7)-y=2(y+1) | | 45+5x=5 | | X+(x-4)+2(x-4)=24 | | y+2.5=.5 | | 5=5x+45 | | 4z+9=-9 | | 7z+8=64 | | 6+18=-y+11 | | 30=q-31 | | 1z+8=13 | | W-7=19 |